1985
DOI: 10.1007/bf01949993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of victorin C, the major host-selective toxin fromCochliobolus victoriae: Structure of degradation products

Abstract: Several host-selective toxins have been isolated in pure form from culture filtrates of Cochliobolus victoriae.Acid hydrolysis of the major toxin, victorin C (apparent mol.wt 796), produced five fragments to which structures 1-5 have been assigned. Spectroscopic techniques revealed that the toxin contains an additional subunit corresponding to 6; thus all the components of victorin C are accounted for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…However, a single experiment showed that it was at least as active as victorin C, 1, from which it differs by an additional chlorine atom in the N-terminal amino acid. Introduction of a six-membered aromatic ring in the Cterminal amino acid residue and removal of two Cl atoms from the N-terminal amino acid residue as in victoricine, 5, reduces the activity of the molecule without affecting its selectivity. Because the biological activity seems to be insensitive to the number of Cl atoms in the N-terminal leucine unit, as judged by comparison of 1 with 2 and 4, the observed reduction of biological activity in victoricine, 5, is likely to be caused largely, if not exclusively, by the change in the C-terminal residue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a single experiment showed that it was at least as active as victorin C, 1, from which it differs by an additional chlorine atom in the N-terminal amino acid. Introduction of a six-membered aromatic ring in the Cterminal amino acid residue and removal of two Cl atoms from the N-terminal amino acid residue as in victoricine, 5, reduces the activity of the molecule without affecting its selectivity. Because the biological activity seems to be insensitive to the number of Cl atoms in the N-terminal leucine unit, as judged by comparison of 1 with 2 and 4, the observed reduction of biological activity in victoricine, 5, is likely to be caused largely, if not exclusively, by the change in the C-terminal residue.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of a six-membered aromatic ring in the Cterminal amino acid residue and removal of two Cl atoms from the N-terminal amino acid residue as in victoricine, 5, reduces the activity of the molecule without affecting its selectivity. Because the biological activity seems to be insensitive to the number of Cl atoms in the N-terminal leucine unit, as judged by comparison of 1 with 2 and 4, the observed reduction of biological activity in victoricine, 5, is likely to be caused largely, if not exclusively, by the change in the C-terminal residue. In fact, comparison of the activities of 1, 3, and 5 suggest that the nature and the substitution pattern on the 12-membered macrocyclic ring is important in the association of the toxin with the host's active-site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations